The Fork Game: A Graphical Interface for Eliciting Higher-Order Risk Preferences - Ergin, Emre; Gürdal, Mehmet Yigit; Kuzubaş, Tolga Umut (Experimental economics : a journal of the Economic Science Association, 2025)
We introduce the “Fork Game,” a graphical interface designed to elicit higher-order risk preferences. In this game, participants connect forked pipes to create a final structure. A ball is then dropped into the top opening of this structure and follows a downward path, randomly turning left or right at each forked joint. This construction is effectively isomorphic to the apportionment of binary-outcome lotteries, allowing participants to construct complex gambles. Furthermore, the game is easily comprehensible, highly modular, and provides a flexible means of assessing risk aversion, prudence, temperance, and even higher-order risk preferences.